Relationship between visual landscape preference and restorative potential of urban landscape - Abkar, Mahdieh (2011)
The role of scenic landscapes in restoring human mental fatigue has begun to receive attention from landscape researchers. However, little is known regarding the role of urban preferred landscapes in increasing their restorative potential to reduce mental fatigue. This study aimed to understand the role of visual preferred landscape on restorative environments. In this experimental study, 120 students from Universiti Putra Malaysia rated 12 color slides of Urban Built Landscape (UBL) and 12 color slides of Urban Natural Landscape (UNL) scenes for 4 restorative components (Being away,Fascination, Coherence, Compatibility), 4 predictors of preferences (Coherence, Complexity, Legibility, Mystery) and 2 criterion variables (PRP and Preference). Results of this study indicated that only three predictors of Preference (Coherence, Complexity, and Mystery) positively explained Preference in UNL and UBL while Legibility did not predict Preference. Coherence was considered as predictor of preference whereas did not predict PRP. Furthermore, the result showed the role of urban natural landscape in increasing restorative potential and Preference of urban environments. Result also showed that only three predictors of preference (Coherence, Complexity,and Mystery) positively explained the restorative components (Being away, Fascination, Compatibility). Theses predictors also positively explained PRP without restorative components in UNL and UBL while “Legibility” negatively explained PRP in UBL; however effect of predictors of preference on PRP in the presence of restorative components reduced and these reductions were in line with mediation. The result of path analysis indicated that effect of “Coherence” and “Complexity” on PRP was fully mediated by the restorative components and Mystery was partially mediated in UNL. In UBL, “Coherence” was fully mediated while “Complexity” and “Mystery” was partially mediated in UBL by the restorative components. This study revealed the role of urban natural landscapes and visual preference for urban landscapes in increasing restorative potential of urban environments that led to reduce mental fatigue. The results of this study can aid city planners, landscape architects and developers with regards to the influence of landscape characteristics in increasing the restorative potential of urban environments. Furthermore, it can is considered for designing new landscapes or improving existing landscapes in cities where we live,work, learn, and go for healing or help.